A Pedagogical Framework For Cognitive Development Via Descriptive Geometry And Digital Tools In Engineering Curricula - Yuldashev Solmonjon Iqboljon ugli (Genius Journals, 2025)
This article explores the theoretical foundations of developing cognitive flexibility in engineering education through the integration of descriptive geometry and digital modeling. The study analyzes the didactic potential of descriptive geometry in cultivating spatial reasoning and visual cognition, and reevaluates its instructional role in light of current pedagogical theories. Emphasis is placed on the use of digital tools such as AutoCAD, SolidWorks, and SketchUp as a means of enhancing graphical thinking, visual interpretation, and metacognitive engagement. The integration of these technologies provides new pathways for activating higher-order thinking skills, fostering student creativity, and bridging the gap between abstract geometric concepts and real-world engineering applications. This paper presents a conceptual framework for advancing engineering education through an interdisciplinary and technologically enriched approach.
Keywords: descriptive geometry; digital modeling; cognitive flexibility